Changes in the ocular surface and meibomian glands following administration of 0.01 and 0.02% atropine - Xueyan Li; Yanying Zhu; Haiyan Xie; Yuexin Chen; Yukun Liu; Xiaochen Xu; Jing Wang (Frontiers in Medicine)
PurposeTo investigate the changes in the ocular surface and meibomian glands following the administration of 0.01 and 0.02% atropine.SettingThe Second Affiliated Hospital of Anhui Medical University, Anhui, China.MethodsIn this randomized controlled study, the 0.01% group (18 patients, 36 eyes) and the 0.02% group (15 patients, 30 eyes) underwent assessments using the Ocular Surface Disease Index (OSDI), Visual Analogue scale (VAS), tear meniscus height (TMH), first noninvasive tear film breakup time (fNIBUT), and average noninvasive tear film breakup time (avNIBUT) at baseline (before administration) and at 1, 3, 6, and 12 months post-treatment. The meibomian glands of both the upper (U) and lower (L) eyelids were evaluated using Meibomian Gland Bio-image Analyzer, measuring parameters such as average gland diameter (avGD), average gland length (avGL), average gland area (avGA), deformation coefficient (DC), and gland visibility score (VS).ResultsThere were no statistically significant differences in any of the parameters within the 0.01% group (all p > 0.05). In the within-group comparisons of the 0.02% group, OSDI was higher at 3 month (p = 0.006) and was lower at 12 months (p = 0.038). VAS was higher at 3 months and 6 months (all p < 0.05). TMH was lower at 12 months (all p < 0.05). U-VS was lower at 3 months (p = 0.006) and higher at 6 and 12 months (all p < 0.05). L-avGL was higher at 1 month (p = 0.001) and lower at 6 months (p = 0.013). L-VS was higher at 6 and 12 months (all p < 0.05). In the 0.02% group, at 3 months, the change in U-VS and L-VS were positively correlated with the change in the VAS (r = 0.542, p = 0.037; r = 0.614, p = 0.015). At 6 months, the change in L-VS was positively correlated with the change in OSDI (r = 0.610, p = 0.016). At 12 months, the change in U-VS was positively correlated with the change in TMH (r = 0.521, p = 0.003).Conclusion0.01% atropine had no significant impact. 0.02% atropine eye drops affected the lipid secretion of meibomian glands, tear meniscus height and subjective discomfort.